The Effectiveness of Twitter As an Interpersonal Communication Media Among Youth in Ambon City - Nahuway, Johana; Tahalele, Olivia; Telussa, Sandra I (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Humans are social beings who need each other and can’t live without others. Communications mainly of interpersonal communication is one requirement that can’t be avoided. With a growing period, the communication can not only be done face to face, but can also be through the medium of communication. One of them is the internet. Twitter is one of the most popular online community, whose members are mostly teenagers can relate to each other to communicate. Twitter's popularity has extended throughout the world and attract the attention of many large communities of Indonesia. Interpersonal Communication Effective communication is needed in order to run well between the two parties. Therefore, research must be done in order to know the effectiveness Twitter as a medium of interpersonal communication among teenagers. By using descriptive quantitative methods, it can be seen that interpersonal communication through Twitter media among adolescents in Ambon city is effective. Keywords: Effectiveness of Interpersonal Communication, Twitter, Media